James Fenimore Cooper ou la frontière mélancolique The Last of the Mohicans et The Leather stocking Tales - Derail, Agnès; Roudeau, Cécile (Actes de la recherche à l'ENS, 2016)
Having long remained in the shadows of academic studies in France, James Fenimore Cooper seems to be returning to the limelight: the inclusion of The Last of the Mohicans on the English 'agrégation' programme (2015-2017) bears witness of such a resurgence. Cooper has made his return, therefore, with a novel which, like the other stories that make up the Leatherstocking Tales, is imbued with a sense of nostalgia for childhood readings. It was one of the first westerns, albeit one without cowboys that takes place in the East. Translated into several languages upon publication, this bestseller, which presented the first of the last American Indians, introduced into the collective imagination the depiction of a New World, deploring its decline and firmly establishing its legendary status. The Last of the Mohicans is not a tale for children that ends badly; it is an uneasy book that inhabits that indecisive limen constituted by the 'frontier'. However, against a backdrop of colonial war, Cooper also waged a literary battle. He invented a national genre that presents a testament to the frontier, with its sublime landscapes, strange characters, and many-hued idiom. Anticipating their disappearance, the text confers upon these figures all the appeal of a lost world, which, only literature and later cinema, would identify with the American myth.